Patiwangi Dalam Upacara Perkawinan di Kota Denpasar - Ni Luh Gede Hadriani (Jayapangus Press, 2022)
Patiwangi in marriage ceremonies between clans has been banned by the government because it was not in accordance with human values. However, until now, patiwangi, there are still Hindu communities in Denpasar who carry out this activity. This study aims to examine the reasons for implementing patiwangi in among the clan smarriage ceremonies and their implications for the lives of the bride and groom and their families. This research includes qualitative research, data collection is done through observation, interviews and documentation. The research data were analyzed descriptively interpretively through three cycles, data reduction, data presentation, and drawing conclusions. The results showed that the patiwangi ceremony was still carried out among the clasn marriage ceremonies by the Hindu community in Denpasar City because they followed the tradition, hoping to create happiness, tranquility, and harmony in family relationships. Patiwangi in among the clans marriage has implications for the religious, socio-cultural, and psychological life of the bride and groom.